2021
DOI: 10.1002/ajb2.1605
|View full text |Cite
|
Sign up to set email alerts
|

Pollinator assemblage and pollen load differences on sympatric diploid and tetraploid cytotypes of the desert‐dominantLarrea tridentata

Abstract: Premise Whole‐genome duplication (polyploidy) is an important force shaping flowering‐plant evolution. Ploidy‐specific plant–pollinator interactions represent important community‐level biotic interactions that can lead to nonrandom mating and the persistence of mixed‐ploidy populations. Methods At a naturally occurring diploid–tetraploid contact zone of the autopolyploid desert shrub Larrea tridentata, we combined flower phenology analyses, collections of bees on plants of known cytotype, and flow cytometry an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…Natural selection could also act on floral traits for differentiated pollinator signals (e.g., Nuismer and Cunningham, 2005). For pollinators to act as a mechanism to facilitate coexistence of cytotypes (Kolář et al, 2017;Sutherland et al, 2020;Laport et al, 2021), the flowers of the cytotypes must differ in ways that pollinators can perceive (e.g., Segraves and Thompson, 1999) or have sufficient morphological differences to facilitate isolation (e.g., Borges et al, 2012). For Gymnadenia conopsea (Orchidaceae), cytotypes differ in floral signals, mainly floral scent (Jersáková et al, 2010;Gross and Schiestl, 2015), and assortative mating has also been observed in some populations (Gross and Schiestl, 2015), suggesting that these mechanisms may function as reproductive isolation mechanisms in mixed populations of autotetraploids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural selection could also act on floral traits for differentiated pollinator signals (e.g., Nuismer and Cunningham, 2005). For pollinators to act as a mechanism to facilitate coexistence of cytotypes (Kolář et al, 2017;Sutherland et al, 2020;Laport et al, 2021), the flowers of the cytotypes must differ in ways that pollinators can perceive (e.g., Segraves and Thompson, 1999) or have sufficient morphological differences to facilitate isolation (e.g., Borges et al, 2012). For Gymnadenia conopsea (Orchidaceae), cytotypes differ in floral signals, mainly floral scent (Jersáková et al, 2010;Gross and Schiestl, 2015), and assortative mating has also been observed in some populations (Gross and Schiestl, 2015), suggesting that these mechanisms may function as reproductive isolation mechanisms in mixed populations of autotetraploids.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, post-pollination mechanisms of isolation may be more important in keeping polyploids distinctive, as in Aster amellus (Asteraceae) (Castro et al, 2011) and for some species little evidence of reproductive isolation is observed (e.g., Barringer and Galloway, 2017). Although pollinator-mediated reproductive isolation between cytotypes has strong theorical support and empirical evidence for some species where it has been measured (e.g., Kennedy et al, 2006;Thompson and Merg, 2008;Roccaforte et al, 2015;Sutherland et al, 2020;Laport et al, 2021), few studies have examined differences in multifaceted floral signals between cytotypes making generalisations challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Theory suggests that niche differentiation is one mechanism by which minority cytotypes may overcome MCE (Fowler and Levin 2016). Niche differentiation among cytotypes has been documented for many species and is linked to both abiotic niche axes (e.g., substrate, elevation, temperature, moisture; Laport et al 2013; López-Jurado, Mateos-Naranjo, and Balao 2019; Wan et al 2019; Decanter et al 2020) and biotic niche axes (e.g., herbivores, pollinators; Münzbergová, Skuhrovec, and Maršík 2015; Laport et al 2016; Muñoz-Pajares et al 2018; Čertner et al 2019; O’Connor, Laport, and Whiteman 2019; Laport, Minckley, and Pilson 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The current distributions with narrow areas of cytotype contact likely represent secondary contact after complex biogeographic histories involving migration and adaptation during glacial and post glacial periods (Hunter et al 2001; Laport, Minckley, and Ramsey 2016), though polyploid cytotypes may be recurrently formed and could represent instances of primary contact (Laport, Minckley, and Ramsey 2016). Although the cytotypes appear to be at least partially ecologically differentiated along several niche axes (e.g., climatic, vegetation communities, herbivore specificity, pollinator visitation; Laport et al 2013; Laport, Minckley, and Ramsey 2016; O’Connor, Laport, and Whiteman 2019; Laport, Minckley, and Pilson 2021) it remains unclear whether such differences are sufficient to maintain sympatry or whether MMND may interact with other niche differences to ease MCE at natural areas of contact.…”
Section: Introductionmentioning
confidence: 99%
“…For example, nuclei of different estimated DNA contents were compared to a reference library of nearby species to identify source species from mixed pollen samples collected in the field from foraging honeybees and bumblebees[56]. In a similar study, pollen load composition was measured on bees foraging in a mixed diploid-tetraploid population[57]. Moon et al[27] suggested using fluorescent protein-tagged lines (FTLs) expressing GFP in their pollen grains, distinguishing pollen from genetically modified and unmodified sources, for rapid and efficient identification of transgene flow.…”
mentioning
confidence: 99%